Unveiling phytostimulation abilities and antifungal metabolites of Trichoderma spp. from avocado rhizosphere soil - Ayyandurai, M; Sangeetha, A (Plant Science Today, 2025)
Trichoderma spp. is a beneficial fungus with agricultural significance, known for its role in plant health enhancement and disease control. This study explores the characterization and phytostimulation abilities of Trichoderma species isolated from avocado plant rhizosphere soil. Ten Trichoderma isolates were obtained through isolation and purification. Their cultural characteristics, such as rapid colony growth and green conidial zones, were assessed, confirming their identity as Trichoderma spp. Biochemical tests revealed their abilities in indole acetic acid (IAA) production (10.2-27.4 µg/mL), phosphate solubilization (17.3-35.8 µg/mL), siderophore production and ammonia production Genomic deoxyribonucleic acid (DNA) extraction and polymerase chain reaction (PCR) amplification using universal primers (ITS1 and ITS4) confirmed their molecular identity, with amplicon sizes ranging from 550 bp to 650 bp. Metabolite analysis of TI-3 via GC-MS uncovered bioactive compounds, including Palmitic acid, 6-pentyl-2H-pyran-2-one, quinoline, phenol, 2-(6-hydrazino-3-pyridazinyl) and heptadecane. Thin Layer Chromatography (TLC) identified distinct antifungal compounds, with an Rf value of 0.84 for chitinase analysis. These findings highlight the multifaceted potential of Trichoderma spp. in promoting plant health and management of diseases, offering valuable insights for sustainable agricultural practices in avocado cultivation.